Size and shape regulation during larval growth in the lepidopteran Pieris brassicae. Issue 1 (10th December 2020) - Fusco, Giuseppe; Rigato, Emanuele; Springolo, Arianna
Abstract: By adopting a longitudinal study design and through geometric morphometrics methods, we investigated size and shape regulation in the head capsule during the larval development of the cabbage butterfly Pieris brassicae under laboratory conditions. We found evidence of size regulation by compensatory growth, although not equally effective in all larval stages. Size compensation is not attained through the regulation of developmental timing, but rather through the modulation of per‐time growth rate. As for the shape, neither the variance of the symmetric component of shape, nor the level of fluctuating asymmetry show any evidence of increase across stages, either at the population or individual level, which is interpreted as a mark of ontogenetic shape regulation. In addition, also the geometry of individual asymmetry is basically conserved across stages. While providing specific documentation on the ontogeny of size and shape variation in this insect, this study may contribute to a more general understanding of developmental regulation and its influence on phenotypic evolution. Abstract : Asymmetric component of the shape of the frons in the plane of the first two between‐group principal components in Pieris brassicae . Minimum convex polygons include the shapes of the four larval stages of each individual. Research Highlights: We investigated the ontogenetic progression of size and shape variation (including fluctuating asymmetry) in the butterfly Pieris brassicae with a longitudinal study‐design. Larval development of this insect shows the mark of several forms of developmental regulation, both in size and shape, which exhibit a certain degree of independence from each other.